The Influence of Communication Skills toward Social Interaction Students in Buddhist College - Iin Avitasari; Wistina Seneru; Edi Sumarwan; Resdhi Wibawa; Rapiadi (Journal of Communication, Religious, and Social Sciences (JoCRSS), 2023)
Effective social interaction is essential to everyday life, especially in an educational environment. Students of Jinarakkhita College of Lampung undergoing lectures need good speaking skills to interact with fellow students and related parties in the campus environment. This study aims to analyze the influence of speaking skills on student social interaction at STIAB Jinarakkhita Lampung. The research method used was a quantitative study using questionnaires distributed to the active student population on the campus. The results showed that the ability to speak significantly influenced the social interaction of students at STIAB Jinarakkhita Lampung. Students with good speaking skills tend to express their thoughts and ideas better clearly and in structure, facilitating effective communication in various social interaction situations. In addition, good speaking skills also affect students' ability to listen well and understand other people's perspectives. With good speaking skills, students can avoid misunderstandings and increase empathy for others, which in turn will strengthen healthy and harmonious social interactions in the campus environment. This research has important implications for academics and decision-makers at STIAB Jinarakkhita Lampung in designing strategies and activities to develop speaking skills for students. By improving speaking skills, it is hoped that social interaction on campus can be improved, create an inclusive environment, support each other, and contribute positively to students' educational experience at STIAB Jinarakkhita Lampung